Magnetic properties of the spin-1 chain compound NiCl3C6H5CH2CH2NH3 - Lipps, F.; Palstra, T.M.; Büchner, B.; Klauss, H.-H.; Vavilova, E.; Salikhov, T.; Günther, M.; Polyakov, A.; Arkenbout, A.H.; Kataev, V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We report experimental results of the static magnetization, ESR and NMR spectroscopic measurements of the Ni-hybrid compound NiCl3C6H5CH2CH2NH3. In this material NiCl3 octahedra are structurally arranged in chains along the crystallographic a axis. According to the static susceptibility and ESR data Ni2+ spins S = 1 are isotropicand are coupled antiferromagnetically (AFM) along the chain with the exchange constant J = 25.5 K. These are important prerequisites for the realization of the so-called Haldane spin-1 chain with the spin-singlet ground state and a quantum spin gap. However, experimental results evidence AFM order at TN ≈ 10 K presumably due to small interchain couplings. Interestingly, frequency-, magnetic field-, and temperature-dependent ESR measurements, as well as the NMR data, reveal signatures which could presumably indicate an inhomogeneous ground state of coexistent mesoscopically spatially separated AFM ordered and spin-singlet state regions similar to the situation observed before in some spin-diluted Haldane magnets.